2016
DOI: 10.1007/s10974-016-9456-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of elementary steps of the cross-bridge cycle in rat papillary muscle fibers expressing α- and β-myosin heavy chain with sinusoidal analysis

Abstract: In mammalian ventricles, two myosin heavy chain (MHC) isoforms have been identified. Small animals express α-MHC, whereas large animals express β-MHC, which contribute to a large difference in the heart rate. Sprague-Dawley rats possessing ~99% α-MHC were treated with propylthiouracil to result in 100% β-MHC. Papillary muscles were skinned, dissected into small fibers, and used for experiments. To understand the functional difference between α-MHC and β-MHC, skinned-fibers were activated under the intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The Pi study characterizes the Pi-release step 5 and the force-generation step 4, which precedes the Pi-release step (Kawai and Halvorson, 1991); 2 πb is sensitive to steps 4 and 5. The results are analyzed in terms of Scheme 1, which is based on six CB states, and which has been successfully used for characterizing rabbit fast-twitch muscle fibers (Kawai and Halvorson, 1991; Kawai and Zhao, 1993; Galler et al, 2005), rabbit slow-twitch muscle fibers (Wang and Kawai, 1996, 1997), and cardiac muscle fibers from rodents (Wang et al, 2013, 2014a; Kawai et al, 2016) and large mammals (Zhao and Kawai, 1996; Fujita et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The Pi study characterizes the Pi-release step 5 and the force-generation step 4, which precedes the Pi-release step (Kawai and Halvorson, 1991); 2 πb is sensitive to steps 4 and 5. The results are analyzed in terms of Scheme 1, which is based on six CB states, and which has been successfully used for characterizing rabbit fast-twitch muscle fibers (Kawai and Halvorson, 1991; Kawai and Zhao, 1993; Galler et al, 2005), rabbit slow-twitch muscle fibers (Wang and Kawai, 1996, 1997), and cardiac muscle fibers from rodents (Wang et al, 2013, 2014a; Kawai et al, 2016) and large mammals (Zhao and Kawai, 1996; Fujita et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is a possibility that the signal of hypophosphorylation of the rod domain may be transmitted to the myosin head domain and contribute to the acceleration of CB kinetics as seen in mutant fibers. Because adult murine ventricles predominantly express the fast a-MHC isoform rather than slow b-MHC isoform (40)(41)(42)(43), it is not likely that myosin isoform switching takes place. We infer from these observations that a Ca 2þ -sensitizing mutation in TnC causes a shift in myosin rod phosphorylation profile.…”
Section: Discussionmentioning
confidence: 99%
“…The α-MHC isoform contracts more vigorously than the β-MHC, albeit at the cost of utilizing more energy. Furthermore, we showed that calcium sensitivity was more attenuated in β-MHC than in α-MHC containing fibers [31]. Our study revealed that the α-MHC isoform predominates in myosin heavy chain in shamcontrol rat hearts (90%), whereas, in comparison, the predominant phenotype is β-MHC in the BDL-cirrhotic heart [16].…”
Section: Abnormal Intracellular Calcium Handling Systemmentioning
confidence: 65%